Changing the role of tutors in distance education with information and communication technologies - Anne Jelfs; Ann Jones; Adrian Kirkwood (Association for Learning Technology, 1996)
The Open University (OU) is a large, complex organization offering many types of course to a wide variety of adult learners. At the time of writing (1995), the university has over 200,000 distance learners, of whom more than 100,000 are taking undergraduate courses. The OU offers more than 140 undergraduate courses and many other courses in Health and Social Welfare, Management, Community Education, etc. There are about 7,700 Tuition and Counselling (TAC) staff throughout Europe.